Maximum Independent Sets Partition of (n,k)-Star Graphs - Fu-Tao Hu (Complexity)
The (n,k)-star graph is a very important computer modelling. The independent number and chromatic number of a graph are two important parameters in graph theory. However, we have not known the values of these two parameters of the (n,k)-star graph since it was proposed. In this paper, we show a maximum independent sets partition of (n,k)-star graph. From that, we can immediately deduce the exact value of the independent number and chromatic number of (n,k)-star graph.